(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article systematizes approaches to the study of the concept of "idioslub" and considers the general and specific features of the terms "idioslub" and "idiolect". The concept of idiosyncratic style is studied cognitively, the components of the writer’s conceptual worldview and the methods of its formation, and the author’s idiosyncratic style are determined. An analysis of the transformation of the metaconcept into a concept is carried out.